The N-terminal domain is required for cell surface localisation of VapA, a member of the Vap family of Rhodococcus equi virulence proteins - Miranda-CasoLuengo, Raul; Yerlikaya, Zeynep; Luo, Haixia; Cheng, Cheng; Blanco, Alfonso; Haas, Albert; Meijer, Wim G. (Public Library Science, 2024)
Rhodococcus equi pneumonia is an important cause of mortality in foals worldwide. Virulent equine isolates harbour an 80-85kb virulence plasmid encoding six virulence-associated proteins (Vaps). VapA, the main virulence factor of this intracellular pathogen, is known to be a cell surface protein that creates an intracellular niche for R. equi growth. In contrast, VapC, VapD and VapE are secreted into the intracellular milieu. Although these Vaps share very high degree of sequence identity in the C-terminal domain, the N-terminal domain (N-domain) of VapA is distinct. It has been proposed that this domain plays a role in VapA surface localization but no direct experimental data provides support to such hypothesis. In this work, we employed R. equi 103S harbouring an unmarked deletion of vapA (R. equi Delta vapA) as the genetic background to express C-terminal Strep-tagged Vap-derivatives integrated in the chromosome. The surface localization of these proteins was assessed by flow cytometry using the THE2122;-NWSHPQFEK Tag FITC-antibody. We show that VapA is the only cell surface Vap encoded in the virulence plasmid. We present compelling evidence for the role of the N-terminal domain of VapA on cell surface localization using fusion proteins in which the N-domain of VapD was exchanged with the N-terminus of VapA. Lastly, using an N-terminally Strep-tagged VapA, we found that the N-terminus of VapA is exposed to the extracellular environment. Given the lack of a lipobox in VapA and the exposure of the N-terminal Strep-tag, it is possible that VapA localization on the cell surface is mediated by interactions between the N-domain and components of the cell surface. We discuss the implications of this work on the light of the recent discovery that soluble recombinant VapA added to the extracellular medium functionally complement the loss of VapA.
Keywords: 17-Kilodalton Antigens; Extracellular Vesicles; Mycobacterium-Tuberculosis; Pathogenicity Island; Plasmid; 15-Kilodalton; Expression; Replication; Temperature; Infection